Regional Policy Coherence for the Great Green Wall Initiative: Reviving Livestock and Pastoral Systems in Africa’s Drylands - Opportunities Within the Great Green Wall Framework - African Union (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
This policy brief explores how the African Union’s Great Green Wall Initiative (GGWI) can serve as a transformative vehicle to revitalise livestock and pastoral systems across Africa’s drylands. These systems are vital for food security, rural livelihoods, ecosystem integrity, and cultural heritage, yet face mounting threats from climate change, land degradation, insecure tenure, and marginalisation. The revised GGWI Strategy and Ten-Year Implementation Framework (2024–2034) recognises the indispensable role of these systems and positions them as central to land restoration and climate resilience efforts. The GGWI Strategy promotes a suite of integrated, landscape-based approaches that link ecological restoration with productive land use. These include evergreen and climate-smart agriculture, pastoral-managed natural regeneration, agrisilviculture, and silvopastoral systems. It also highlights livestock-specific practices such as participatory rangeland management, holistic planned grazing, adaptive multi-paddock grazing, regenerative grazing, controlled grazing, and exclosures. The GGWI’s four strategic intervention axes collectively provide a robust framework for integrating pastoral systems into sustainable land restoration. Axis 1 promotes inclusive governance and participatory leadership, ensuring that pastoralist voices shape policy and implementation. Axis 2 embeds livestock systems into landscape restoration by advancing agroecological practices, strengthening value chains, and supporting nature-based enterprises. Axis 3 focuses on creating an enabling environment through multi-sectoral coordination, inclusive capacity development, and adaptive planning. Axis 4 aligns GGWI efforts with regional and global frameworks - such as the African Union Policy Framework for Pastoralism, the International Year of Rangelands and Pastoralists (2026), and flagship initiatives like the World Bank Regional Sahel Pastoralism Support project (PRAPS-2) and Sustainable Investments for Large-Scale Rangeland Restoration (STELARR) - to amplify impact and foster knowledge exchange. Grounded in adaptive practices, local knowledge, and multi-level collaboration, the GGWI Strategy offers a comprehensive and inclusive roadmap for restoring rangelands, strengthening farmer and pastoral livelihoods, and achieving climate-resilient development in Africa’s drylands.